2016
DOI: 10.3732/ajb.1600142
|View full text |Cite
|
Sign up to set email alerts
|

Common mycelial networks impact competition in an invasive grass

Abstract: Our results indicate that the presence of CMN networks can have positive effects on B. sylvaticum establishment and nutrient status, which may affect plant competition and invasion success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Our results indicate that the presence of AM fungi enhanced the competitive ability of invasive E. sphaerocephalus against native I. conyzae. This is in agreement with Callaway et al 59 , and Workman and Cruzan 60 who reported positive effects of AM fungi on biomass www.nature.com/scientificreports/ production of invasive Centaurea melitensis and Brachypodium sylvaticum, respectively, growing in competition with native plants. Contrary to our second hypothesis, the difference between the M+ and M− treatments was more pronounced in plants grown in experimentally disturbed soil.…”
Section: Discussionsupporting
confidence: 90%
“…Our results indicate that the presence of AM fungi enhanced the competitive ability of invasive E. sphaerocephalus against native I. conyzae. This is in agreement with Callaway et al 59 , and Workman and Cruzan 60 who reported positive effects of AM fungi on biomass www.nature.com/scientificreports/ production of invasive Centaurea melitensis and Brachypodium sylvaticum, respectively, growing in competition with native plants. Contrary to our second hypothesis, the difference between the M+ and M− treatments was more pronounced in plants grown in experimentally disturbed soil.…”
Section: Discussionsupporting
confidence: 90%
“…However, these effects vanished when the plants were grown at higher densities [ 19 ]. This suggests that there is an interaction between mycorrhizal colonisation in the roots and plant density and the existence of shared mycelial networks [ 20 ], which ultimately affect the outcome of plant competition and invasion success. How mycorrhizal colonisation affects the outcome of plant interspecific competition depends to a large extent on the mycorrhizal affinity of the dominant and sub-dominant species.…”
Section: Introductionmentioning
confidence: 99%
“…Most parasitized host plants can still form symbiotic relationships with arbuscular mycorrhizal fungi (AMF), and have common mycorrhizal networks (CMNs) with neighboring plants (Egerton-Warburton et al 2007, Mikkelsen et al 2008, Weremijewicz and Janos 2013. CMNs play an important role in plant interactions by regulating the distribution of mineral nutrients between interconnected plant individuals (Egerton-Warburton et al 2007, Mikkelsen et al 2008, Weremijewicz and Janos 2013, Workman and Cruzan 2016. However, whether changes in nutrient distribution by CMNs provide a mechanistic link for cascading effects of parasites on neighboring plants of the host plants is not known.…”
Section: Introductionmentioning
confidence: 99%